Estimated reductions in hospitalizations and deaths from childhood diarrhea following implementation of rotavirus vaccination in Africa - Minesh P. Shah; Jacqueline E. Tate; Jason M. Mwenda; A. Duncan Steele; Umesh D. Parashar (Expert Review of Vaccines, 2017)
Introduction: Rotavirus is the leading cause of hospitalizations and deaths from diarrhea. 33 African countries had introduced rotavirus vaccines by 2016. We estimate reductions in rotavirus hospitalizations and deaths for countries using rotavirus vaccination in national immunization programs and the potential of vaccine introduction across the continent. Areas covered: Regional rotavirus burden data were reviewed to calculate hospitalization rates, and applied to under-5 population to estimate baseline hospitalizations. Rotavirus mortality was based on 2013 WHO estimates. Regional pre-licensure vaccine efficacy and post-introduction vaccine effectiveness studies were used to estimate summary effectiveness, and vaccine coverage was applied to calculate prevented hospitalizations and deaths. Uncertainties around input parameters were propagated using boot-strapping simulations. In 29 African countries that introduced rotavirus vaccination prior to end 2014, 134,714 (IQR 112,321–154,654) hospitalizations and 20,986 (IQR 18,924–22,822) deaths were prevented in 2016. If all African countries had introduced rotavirus vaccines at benchmark immunization coverage, 273,619 (47%) (IQR 227,260–318,102) hospitalizations and 47,741 (39%) (IQR 42,822–52,462) deaths would have been prevented. Expert commentary: Rotavirus vaccination has substantially reduced hospitalizations and deaths in Africa; further reductions are anticipated as additional countries implement vaccination. These estimates bolster wider introduction and continued support of rotavirus vaccination programs.